The Role of Family Christian Religious Education (PAK) in Human Resource Development and Economic Empowerment of the Church through the Wooden House Industry in Sion Woloan Congregation, Tomohon Dua Region: Peran Pendidikan Agama Kristen (PAK) Keluarga dalam Pengembangan Sumber Daya Manusia dan Pemberdayaan Ekonomi Jemaat melalui Industri Rumah Kayu di Jemaat Sion Woloan Wilayah Tomohon Dua - Jefry Kalalo (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This study examines the impact of Christian Religious Education (PAK) on human resource development and economic empowerment among congregations via the wooden house sector in GMIM Sion Woloan. Prior research has underscored PAK's substantial impact on moral and character development in familial contexts; nevertheless, its relevance to particular economic behaviors is still inadequately examined. This study examines how PAK influences the development of positive attitudes towards work and social responsibility within family life and its effect on enhancing economic welfare. The research utilizes a descriptive qualitative methodology, employing a phenomenological method to document the subjective experiences of 30 participants, comprising parents, children, and church leaders engaged in PAK activities and the wooden house industry. Data were gathered via semi-structured interviews and focus group discussions, concentrating on the integration of PAK ideals into quotidian economic practices. Thematic analysis was utilized to discern emergent themes concerning the interplay between religious education, human resource development, and economic activities. The findings indicate that PAK cultivates a robust work ethic and interpersonal connections within families, enhancing both personal character development and economic advancement. The results underscore the necessity for intensified collaboration between religious organizations and local industry to optimize the potential of PAK in improving community welfare.